2009
DOI: 10.1016/j.actamat.2008.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the development of anisotropic grain boundary character distributions during normal grain growth

Abstract: Grain boundaries in polycrystalline magnesia-doped alumina and yttrium aluminum garnet were classified as growing in area or shrinking in area on the basis of topology and curvature considerations. Measurements of dihedral angles at grain boundary thermal grooves were used to determine that the energies of the growing boundaries are, on average, lower than the energies of the shrinking boundaries. The observations also show that the length of a boundary is inversely correlated to its energy. The findings sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 53 publications
(36 reference statements)
2
64
0
Order By: Relevance
“…Nonuniform grain boundary mobility has been explored in the context of grain boundary energy [61][62][63] with implications for the formation of anisotropic grain boundary character distributions. 64 In nanocrystalline Ni, abnormal grain growth has been attributed to the preferential migration of high-mobility coincident site lattice (CSL) boundaries. 21 Boundary fractions could not be quantified for the bimodal structures due to the aforementioned reliability issues; however, analysis of the boundary fractions from Fig.…”
Section: Fig 6 Inverse Pole Figures For the Combined Reliability-ormentioning
confidence: 99%
“…Nonuniform grain boundary mobility has been explored in the context of grain boundary energy [61][62][63] with implications for the formation of anisotropic grain boundary character distributions. 64 In nanocrystalline Ni, abnormal grain growth has been attributed to the preferential migration of high-mobility coincident site lattice (CSL) boundaries. 21 Boundary fractions could not be quantified for the bimodal structures due to the aforementioned reliability issues; however, analysis of the boundary fractions from Fig.…”
Section: Fig 6 Inverse Pole Figures For the Combined Reliability-ormentioning
confidence: 99%
“…The anisotropic characteristics of the energy have been recognized since at least the time of Smith [9] and it has recently been shown that the probability that a grain boundary is annihilated during grain growth is related to its energy, and this leads to an anisotropic distribution of grain boundary types [10]. The energy anisotropy arises because different grain boundaries have different microscopic structures; following the line of reasoning that leads to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, evolution in grain boundary/surface energy ratio due to segregation impurity, for example, has been invoked as an explanation for the change in the groove-root angle with time (Zhang et al, 2002). Also, the blunting effect of grain-boundary migration on root angles (Dillon and Rohrer, 2009) might contribute to the evolution.…”
Section: Groove-root Anglesmentioning
confidence: 99%
“…Yet, growth and shrinkage of grains may in principle affect root angles (Dillon and Rohrer, 2009). While our samples do not exhibit "abandoned" grooves as evidence for grain boundary migration, the partially blunted roots of grooves may be associated with grain boundary migration (Rabkin et al, 2006) .…”
Section: Experimental Limitationsmentioning
confidence: 99%